Some Notes on Critical Appraisal of Prevalence Studies; Comment on: "The Development of a Critical Appraisal Tool for Use in Systematic Reviews Addressing Questions of Prevalence" - Thomas Harder (Kerman University of Medical Sciences, 2014)
Decisions in healthcare should be based on information obtained according to the principles of Evidence-Based Medicine (EBM). An increasing number of systematic reviews are published which summarize the results of prevalence studies. Interpretation of the results of these reviews should be accompanied by an appraisal of the methodological quality of the included data and studies. The critical appraisal tool for prevalence studies developed and tested by Munn et al. comprises 10 items and aims at targeting all kinds of prevalence studies. This comment discusses the pros and cons of different designs of quality appraisal tools and highlights their importance for systematic reviews of prevalence studies. Beyond piloting, which has been performed in the study by Munn et al., it is suggested here that the validity of the tool should be tested, including reproducibility and inter-rater reliability. It is concluded that studies as the one by Munn et al. will help to establish a critical understanding of methodological quality and will support the use of systematic reviews of non-intervention studies for health policy making.